Association Between Different Indicators of Obesity and Depression in Adults in Qingdao, China: A Cross-Sectional Study - Cui, Jing; Sun, Xiufen; Li, Xiaojing; Ke, Ma; Sun, Jianping; Yasmeen, Nafeesa; Khan, Jamal Muhammad; Xin, Hualei; Xue, Shouyong; Baloch, Zulqarnain (Frontiers in Endocrinology, 2018)
Background: This study was designed to investigate the perceived relationship between body weight and depression risk in a Chinese population in Qingdao, China. Methods: A population-based cross-sectional survey was performed with 4573 participants (between 35-74 years) from the year 2009 to 2012 in Qingdao, China. We applied Zung self-rating depression scale to ascertain the level of depression in participants. The associations between different indicator of obesity (BMI, WC, and WHR) and depression were assessed by logistic regression based on the Chinese criteria of obesity. Sensitivity analysis was done based on the Asian and WHO criteria of obesity. Results: The Zung score of 243 participants (5.2%) were over 45 and entitled as depression. Furthermore, multi-variable logistic analyses revealed that being overweight [odds ratios (OR): 1.48, 95% confidence intervals (95% CI): 1.08–2.03] and abdominal obesity (WC category in Chinese criteria) (OR: 1.47, 95% CI: 1.08-2.00) was significantly associated with chances for a higher risk for depression compared to normal weight subjects. Sensitivity analysis revealed that abdominal obesity (Asian criterion) (OR: 1.41, 95% CI: 1.03-1.91) was a significant risk factor for depression. Similarly, overweight (WHO criterion) (OR: 1.39, 95% CI: 1.03-1.87) was an obvious risk factor for depression. Conclusion: Overweight and abdominal obesity (WC category) were found linked with a higher risk of depression. However, abdominal obesity (WHR category) was not associated with depression.